Historical Aspects of the Statutory Regulation of Financial Inclusion for the Poor and Low-Income Earners in South Africa: Array - Chitimira, Howard (Acta Universitatis Danubius. Œconomica, 2020)
The article discusses the regulation of financial inclusion for the poor and low-income earners prior to, and after democracy in South Africa. Therefore, relevant practices and regulatory measures that were adopted in a bid to curb financial exclusion of the poor and low-income earners in South Africa, particularly after the attainment of democracy are examined. Furthermore, the article explores whether the poor and low-income earners are still financially excluded from accessing basic financial products and financial services in South Africa. Accordingly, various statutes such as National Credit Act 34 of 2005 as amended by the National Credit Amendment Act 7 of 2019 (NCA), the now repealed Usury Act 73 of 1968 (Usury Act), the Credit Agreements Act 75 of 1980 (Credit Act), the now repealed Financial Services Board Act 97 of 1990 (FSB Act), the South African Reserve Bank Act 90 of 1989 (SARB Act), the Banks Act 94 of 1990 (Banks Act), the Consumer Protection Act 68 of 2008 (CPA) and the Financial Sector Regulation Act 9 of 2017 (FSRA) are discussed. To this end, the gaps and flaws in the relevant practices and regulatory measures that were adopted under these and other related statutes to promote financial inclusion of the poor and low-income earners in South Africa are outlined and discussed. Keywords: financial inclusion, poor and low-income earners, financial exclusion, stokvel, regulation.